2006
DOI: 10.1021/bi052414g
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular and Mechanical Properties of Egg Case Silk from Wasp Spider, Argiope bruennichi

Abstract: Araneoid spiders use specialized abdominal glands to produce up to seven different protein-based silks/glues that have various mechanical properties. To date, the fibroin sequences encoding egg case fibers have not been fully determined. To gain further understanding of a recently reported spider silk protein gene family, several novel strategies were utilized in this study to isolate two full-length cDNAs of egg case silk proteins, cylindrical silk protein 1 (CySp1, 9.1 kb) and cylindrical silk protein 2 (CyS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 36 publications
3
54
0
Order By: Relevance
“…N-terminal fragments (Ϸ200 bp) of TuSp1 were obtained, respectively, from a genomic DNA and cDNA library by PCR using degenerated primer sets (5Ј-ATG GTT TGG RTN ACN XYN ATQ GC-3Ј and 5Ј-RTC XTG XTG XTC XTG RAA NGG RAA-3Ј) designed on the basis of the conserved amino acid sequences of the N termini from known TuSp1s (1,28). One of the two fragments obtained from genomic DNA was the same as the one from the cDNA library.…”
Section: Methodsmentioning
confidence: 99%
“…N-terminal fragments (Ϸ200 bp) of TuSp1 were obtained, respectively, from a genomic DNA and cDNA library by PCR using degenerated primer sets (5Ј-ATG GTT TGG RTN ACN XYN ATQ GC-3Ј and 5Ј-RTC XTG XTG XTC XTG RAA NGG RAA-3Ј) designed on the basis of the conserved amino acid sequences of the N termini from known TuSp1s (1,28). One of the two fragments obtained from genomic DNA was the same as the one from the cDNA library.…”
Section: Methodsmentioning
confidence: 99%
“…GPGX n repeats, which are found in MaSp2 and Flag silk, have been hypothesized to form ␤ turn structures, which provide extensibility to the threads (14). To date, the only reported full-length gene sequences from the spider silk family include masp1, masp2, and cysp1 (11,18). These gene sequences are known to encode large molecular mass proteins, with their corresponding predicted molecular masses representing 250, 311, and 277 kDa, respectively.…”
mentioning
confidence: 99%
“…MS/MS 4 analyses of black widow peptides generated from solubilized egg case materials digested with trypsin have shown that the large diameter core fibers contain the fibroin TuSp1, as well as the egg case proteins ECP-1 and ECP-2 (egg case protein 1 or 2), which form a trimeric complex in cob weavers (14,16,17). Real time quantitative PCR and Northern blot analyses have demonstrated tubuliform-restricted patterns of expression for these gene products (14,(17)(18)(19). Although it has been widely accepted by the silk community that the aciniform glands produce egg case silk constituents and wrapping silk, no molecular evidence has been reported to demonstrate that aciniform-specific fibroins are directly assembled into these diverse materials (1).…”
mentioning
confidence: 99%